Pengaruh Variasi Kadar Humus Tanah Terhadap Retensi Air Dan Ketersediaan Nutrisi - Zebua, Irifan Setia; Gea, Irvan Haviz (Jurnal Ilmu Pertanian dan Perikanan, 2024)
This research aims to examine the effect of variations in humus content on water retention and nutrient availability (N, P and K) in the soil. This research used a laboratory experimental design with humus content treatments of 0%, 2%, 5%, and 10%. The results showed that increasing humus levels significantly increased the water retention capacity and availability of soil nutrients. At a humus content of 10%, soil has the highest capacity to hold water and provide essential nutrients for plants. This shows that humus plays an important role in supporting the balance between water retention and nutrient release, which is very important for agricultural productivity. In conclusion, increasing humus levels through organic matter or green manure can improve soil quality and support sustainable agriculture, especially on land with low humus levels.